The 2008 Methoni earthquake sequence: the relationship between the earthquake cycle on the subduction interface and coastal uplift in SW Greece. Issue 3 (9th December 2016) - Howell, Andy; Palamartchouk, Kirill; Papanikolaou, Xanthos; Paradissis, Demitris; Raptakis, Costas; Copley, Alex; England, Philip; Jackson, James
Abstract: Seismological, GPS and historical data suggest that most of the 40 mm yr −1 convergence at the Hellenic Subduction Zone is accommodated through aseismic creep, with earthquakes of M W ≲ 7 rupturing isolated locked patches of the subduction interface. The size and location of these locked patches are poorly constrained despite their importance for assessment of seismic hazard. We present continuous GPS time-series covering the 2008 M W 6.9 Methoni earthquake, the largest earthquake on the subduction interface since 1960. Post-seismic displacements from this earthquake at onshore GPS sites are comparable in magnitude with the coseismic displacements; elastic-dislocation modelling shows that they are consistent with afterslip on the subduction interface, suggesting that much of this part of the interface is able to slip aseismically and is not locked and accumulating elastic strain. In the Hellenic and other subduction zones, the relationship between earthquakes on the subduction interface and observed long-term coastal uplift is poorly understood. We use cGPS-measured coseismic offsets and seismological body-waveform modelling to constrain centroid locations and depths for the 2008 Methoni M W 6.9 and 2013 Crete M W 6.5 earthquakes, showing that the subduction interface reaches the base of the seismogenic layer SW of the coast of Greece. These earthquakes caused subsidence of the coast in regions where the presence of Pliocene–Quaternary marine terraces indicates recent uplift, so we conclude that deformation associated with the earthquake cycle on the subduction interface is not the dominant control on vertical motions of the coastline. It is likely that minor uplift on a short length scale (∼15 km) occurs in the footwalls of normal faults. We suggest, however, that most of the observed Plio-Quaternary coastal uplift in SW Greece is the result of thickening of the overriding crust of the Aegean by reverse faulting or distributed shortening in the accretionary wedge, by underplating of sediment of the Mediterranean seafloor, or a combination of these mechanisms.